Influence of Supplemental Dietary Poultry Fat, Phytase and 25-hydroxycholecalciferol on the Blood Characteristics of Commercial Layers Inoculated Before or at the Onset of Lay with F-strain Mycoplasma gallisepticum - Peebles, E.D.; Park, S.W.; Branton, S.L.; Gerard, P.D.; Womack, S.K. (International Journal of Poultry Science, 2010)
The effects of 2 supplemental levels of dietary Poultry Fat (PF) and the combination of PF, phytase (PHY) and 25-hydroxycholecalciferol [25(OH)D] on the blood characteristics of commercial layers inoculated with F-strain Mycoplasma gallisepticum (FMG) were investigated in 2 trials. Sham and FMG inoculations were administered at 12 (before lay) and 22 (early in lay) wk and dietary treatments [Basal Control Diet (BCD); BCD with 0.75% supplemental PF (LPFD); BCD with 1.50% supplemental PF (HPFD); HPFD additionally supplemented with 0.013% PHY and 0.025% 25(OH)D] were initiated at 20 wk of age. Whole blood hematocrit and plasma protein, serum cholesterol, serum triglycerides and serum calcium concentrations were determined at 24, 34, 44, 50 and 58 wk of age. There were no treatment effects on any of the parameters examined except for serum triglyceride and calcium concentrations. Regardless of the age at which the layers were inoculated (12 or 22 wk), when compared with a sham-inoculation, an FMG inoculation reduced the serum concentrations of triglycerides at 24 wk of age and calcium at 34 wk of age, but subsequently increased serum calcium concentrations at 58 wk of age. In conclusion, inoculation with FMG before or early in lay resulted in decreases in serum triglycerides early in lay and respective decreases and increases in serum calcium concentrations during the peak and late periods of lay. Furthermore, the use of 1.50% supplemental dietary PF alone or in combination with supplementary PHY and 25(OH)D had no effect on the blood parameters investigated throughout lay in birds that did or did not receive FMG inoculations at 12 or 22 wk of age.